PERAN HUKUM DAN FUNGSI BADAN USAHA MILIK NEGARA (BUMN) DALAM PEREKONOMIAN NASIONAL - Abdul Rauf (JOURNAL OF LAW AND NATION, 2025)
This study aims to analyse the legal role and function of State-Owned Enterprises (SOEs) in supporting the national economy in accordance with the mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia. As state-owned economic entities, SOEs have two main functions, namely legal and economic functions, which are interrelated. The legal function plays a role in structuring, supervising, and managing SOEs to ensure they operate in accordance with the principles of transparency, accountability, and public interest. Meanwhile, the economic function of SOEs is evident in their contribution to gross domestic product (GDP) growth, employment, infrastructure development, and equitable distribution of wealth. This study uses a literature review method with a normative juridical approach based on an analysis of legislation, academic literature, and official government documents. The results of the study show that the success of SOEs in carrying out their functions is highly dependent on the effectiveness of the legal system that regulates them and the consistent application of the principles of good corporate governance. With the support of a strong legal framework, SOEs can optimally function as state economic actors and instruments of equitable and sustainable national development.